Penerapan Model Pembelajaran Berbasis Proyek Pada Pembelajaran E-Learning Materi Kesetimbangan Kimia - Gultom, Elisabet Rosmadelila; Muchtar, Zainuddin (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research aims to analyze the effect of the application of project-based learning models on e-learning chemical equilibrium material on learning outcomes, student activities and student responses. This type of research is a quasi-experimental with a pretest-posttest control group design. This research was conducted in January 2022. Data collection techniques were obtained by means of tests, observation sheets, questionnaires, and documentation. The population of this research is the students of class XI IPA SMA Negeri 9 Medan. The research sample consisted of 2 classes with a total of 65 students with a random sampling technique. The experimental class was given learning using a project-based learning model in e-learning, the control class was given learning using a direct learning model. This study shows the following results: (1) there is a positive effect of implementing project-based learning models on e-learning chemical equilibrium material on improving student learning outcomes, obtained tcount = 9.91 > ttable = 1.669 and class N-gain value the experimental class is 0.77 with the high category, while the N-gain for the control class is 0.56 in the medium category. (2) student learning activities in the experimental class are very positive or very good towards, the average percentage is 81.83% with the qualification "very good". (3) students in the experimental class showed a positive or good response in the learning process that took place in the classroom, the average percentage of responses was 76.55% with "good" qualifications. This shows that the project-based learning model in e-learning is good for use in the teaching and learning process.